Characterization of plasma labile heme in hemolytic conditions. (11th September 2017) - Gouveia, Zélia; Carlos, Ana R.; Yuan, Xiaojing; Aires‐da‐Silva, Frederico; Stocker, Roland; Maghzal, Ghassan J.; Leal, Sónia S.; Gomes, Cláudio M.; Todorovic, Smilja; Iranzo, Olga; Ramos, Susana; Santos, Ana C.; et al.
Abstract : Extracellular hemoglobin, a byproduct of hemolysis, can release its prosthetic heme groups upon oxidation. This produces metabolically active heme that is exchangeable between acceptor proteins, macromolecules and low molecular weight ligands, termed here labile heme. As it accumulates in plasma labile heme acts in a pro‐oxidant manner and regulates cellular metabolism while exerting pro‐inflammatory and cytotoxic effects that foster the pathogenesis of hemolytic diseases. Here, we developed and characterized a panel of heme‐specific single domain antibodies (sdAbs) that together with a cellular‐based heme reporter assay, allow for quantification and characterization of labile heme in plasma during hemolytic conditions. Using these approaches, we demonstrate that when generated during hemolytic conditions labile heme is bound to plasma molecules with an affinity higher than 10 −7 m and that 2–8% (~ 2–5 μm ) of the total amount of heme detected in plasma can be internalized by bystander cells, termed here bioavailable heme. Acute, but not chronic, hemolysis is associated with transient reduction of plasma heme‐binding capacity, that is, the ability of plasma molecules to bind labile heme with an affinity higher than 10 −7 m . The heme‐specific sdAbs neutralize the pro‐oxidant activity of soluble heme in vitro, suggesting that these maybe used to counter the pathologic effects of labile heme during hemolytic conditions. Finally, we show that heme‐specific sdAbs can be used to visualize cellular heme. In conclusion, we describe a panel of heme‐specific sdAbs that when used with other approaches provide novel insights to the pathophysiology of heme. Abstract : During hemolysis, extracellular hemoglobin can release its heme groups upon oxidation. The resulting labile heme is exchanged between different plasma acceptor proteins, macromolecules and low molecular weight ligands. Arrows indicate heme transfer from lower to higher affinity acceptors. Interactions are not at scale nor accurate according to crystal structures. Heme affinities are indicative for human plasma acceptors.